Conceptions of health: A cross-cultural comparison. - Levesque, Annabel (Author); Li, Han (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
The purpose of this study was to investigate the health views of Anglophones and Francophones of European ancestry as well as First Nations individuals living in an urban setting. A total of 60 participants were individually interviewed. The first objective of the research was to understand how the interviewees defined health. They provided a multidimensional definition of health that departs from the biomedical model, arguing that health is more than the absence of illness and that it encompasses the whole person, not only the body. The second objective of the study was to gain a better understanding of the participants\u2019 health practices. Many argued that one needs to be proactive in order to be healthy and explained that health practices should be tailored in accordance with one\u2019s particular needs. They especially emphasized the importance of having a healthy lifestyle. The third objective of the research was to investigate cultural differences in health definitions and practices. While Anglophones and Francophones talked about health from an individual perspective, First Nations interviewees provided a definition of health that expands beyond the boundaries of the individual self. They also emphasized spiritual and developmental health, while Anglophones and Francophones placed more importance on physical health. Francophones and First Nations interviewees reported promoting their health by maintaining their traditions and culture. The fourth objective of the study was to explore the extent to which definitions of health are related to health practices. The findings indicated that some of the health definitions could significantly predict the participants\u2019 health practices. The research findings suggest that culture should be taken into consideration in order to provide culturally appropriate health care and to develop health policies and programs that reflect the concerns of members of various cultures. The present study advances knowledge by (a) proposing a new health definition that expands ...